Effect of Interviews Done by Intensive Care Physicians on Organ Donation - (:unkn) unknown (Elsevier USA, 2017)
In this study, we examined the correspondence between intensive care unit physicians and the relatives of potential brain-dead donors regarding the decision to donate or the reasons for refusing organ donation. A total of 12 consecutive cases of potential brain-dead patients treated in intensive care units of Marmara University Pendik Education and Research Hospital in 2013 were evaluated. For each of the cases, the Potential Donor Questionnaire, and Family Notification, Brain Death Criteria Fulfilment and Organ Donation Conversation Questionnaires were used to collect the required data. Statistically, descriptive analyses were performed. We concluded that honestly, regularly, and sufficiently informed relatives of the potential brain-dead donor more readily donate organs, with a positive contribution from the intensive care physician. © 2017 Elsevier Inc.